Relevance of Hasan al-Banna’s Viewpoint on Islamic Education through Nizam al-Usrah on Character Building - Naufal Ahmad Rijalul Alam; Nur Bakri Abd Hamid (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2024)
Technology advancements are acknowledged to make it simpler for young learners to access information and knowledge, but they also lead to a change in values in people's outlook on life and their religious practices due to a leaning towards freedom and hyper technology. Islamic education must act in response to these circumstances by implementing a number of tactical measures to transform the difficulties encountered into opportunities in an endeavour to raise an excellent generation that is morally upright and intelligent. This article will discuss the crucial function of Islamic education in fostering responsibility in the face of rapidly advancing technological advancements in both communication and educational resources from the perspective of Hasan al-Banna. This article uses library research techniques to gather a variety of ideas, facts, research findings, and expert opinions along with pertinent analysis. As a result, it is clear how Hasan al-Banna’s viewpoints on Islamic education is in producing a generation that is excellent in every way, including intellectually, materially, morally, and spiritually, where they are collected to the character building. Abstrak: Kemajuan teknologi diakui telah memudahkan pelajar muda untuk mengakses informasi dan pengetahuan, namun juga membawa perubahan nilai-nilai dalam pandangan hidup masyarakat dan praktik keagamaan mereka akibat kecenderungan menuju kebebasan dan hiper teknologi. Pendidikan Islam harus merespons kondisi ini dengan menerapkan sejumlah langkah taktis untuk mengubah kesulitan yang dihadapi menjadi peluang dalam upaya mendidik generasi yang unggul secara moral dan cerdas. Artikel ini akan membahas peran penting pendidikan Islam dalam membentuk tanggung jawab menghadapi kemajuan teknologi yang pesat dalam komunikasi dan sumber daya pendidikan, ditinjau dari perspektif Hasan al-Banna. Artikel ini menggunakan teknik penelitian pustaka untuk mengumpulkan berbagai ide, fakta, temuan penelitian, dan pandangan ahli beserta analisis yang relevan. Sebagai hasilnya, jelas bagaimana pandangan Hasan al-Banna tentang pendidikan Islam berkontribusi dalam menciptakan generasi yang unggul dalam segala hal, termasuk secara intelektual, materi, moral, dan spiritual yang semuanya tergabung dalam pembangunan karakter.